Risk Factor Profiles in Patients with Different Clinical Manifestations of Venous Thromboembolism: A Focus on the Factor V Leiden Mutation - Manten, Bert; Westendorp, Rudi G J; Koster, Ted; Reitsma, Pieter H; Rosendaal, Frits R (Thrombosis and Haemostasis, 1996)
Background. Patients with venous thromboembolic disease may present with different clinical manifestations. Factor V Leiden mutation leading to resistance to activated protein C is associated with a sevenfold increased risk for presenting with deep-vein thrombosis. It is not yet established whether carriers of the mutation have a similarly increased risk for manifesting with pulmonary embolism.Methods. From an Anticoagulation Clinic monitoring coumarin therapy, a consecutive series of patients with a first thromboembolic event (objectively proven by current radiological methods) were enrolled. All patients were interviewed and blood was drawn for geno-typing. From the hospital charts and the personal interview, information was obtained on acquired risk factors and the signs and symptoms on hospital admission.Results. 45 patients presented with symptoms of pulmonary embolism only, 211 had only symptoms of deep-vein thrombosis whereas 23 had clinical features of both. In about half of the patients acquired risk factors for venous thromboembolism were present which did not differ between the three groups of patients. Recent surgery had been performed more often in patients presenting with pulmonary embolism than in other patients (33.3% vs. 18.5%, p <0,05). Factor V Leiden was present in 9% of the patients presenting with pulmonary embolism (relative risk: 3.3 95% Cl: 1.0-10.6) and 17% of the patients presenting with deep-vein thrombosis (relative risk: 6.9 95% Cl: 3.6-12.8). The prevalence of factor V Leiden was intermediate in patients with both clinical characteristics.Conclusion. These data suggest that patients with venous thromboembolism have different clinical presentation depending on the risk factor profile. Factor V Leiden may preferentially lead to manifest deep-vein thrombosis. Differences in structure of venous thrombi could underlie differences in embolic tendency.